English Language Education for Intercultural Communication: A Course Study in Alauddin State Islamic University - Neelam Nisar; Mehartab Rabica; Muhammad Ali Adam (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study evaluates the effectiveness of the course English for Intercultural Communication in enhancing English proficiency and intercultural communicative competence among students at Alauddin State Islamic University, Makassar, Indonesian. It also explores pedagogical practices and students’ preparedness for intercultural communication in multicultural contexts. Methodology: This study employed a qualitative research design. Data were collected through teacher interviews, classroom observations, and document analysis. The analyzed documents included curriculum materials, assessment instruments, and students’ feedback. No software, survey instrument, or review method was used in this study. Main Findings: The findings provide critical insights into prevailing practices and challenges in the instruction of English for intercultural communication in Indonesian. The study identifies areas for improving curriculum design, pedagogical strategies, and educational policy while supporting educational stakeholders in preparing students for global citizenship through English language education in multicultural contexts. Novelty/Originality of this study: This study examines English as a vehicle for intercultural communication by focusing on both pedagogical practices and students’ preparedness within the English for Intercultural Communication course at Alauddin State Islamic University. The findings contribute practical recommendations for curriculum design, pedagogy, and educational policy in multicultural English language education